Primary Empty Sella. Issue 10 (10th October 2020) - Mehla, Sandhya; Chua, Abigail L.; Grosberg, Brian; Evans, Randolph W.
Abstract : Primary empty sella (PES) syndrome is a misnomer as it is not a syndrome but a radiological finding with possible endocrine abnormalities. No specific headache type has been shown to be caused by PES. Endocrine screening may be considered for asymptomatic persons with PES.